Self-Organization of Polymeric Fluids in Strong Stress Fields - A. V. Semakov; V. G. Kulichikhin; A. Y. Malkin (Advances in Condensed Matter Physics)
Analysis of literature data and our own experimental observations have led to the conclusion that, at high deformation rates, viscoelastic liquids come to behave as rubbery materials, with strong domination by elastic deformations over flow. This can be regarded as a deformation-induced fluid-to-rubbery transition. This transition is accompanied by elastic instability, which can lead to the formation of regular structures. So, a general explanation for these effects requires the treatment of viscoelastic liquids beyond critical deformation rates as rubbery media. Behaviouristic modeling of their behaviour is based on a new concept, which considers the medium as consisting of discrete elastic elements. Such a type of modeling introduces a set of discrete rotators settled on a lattice with two modes of elastic interaction. The first of these is their transformation from spherical to ellipsoidal shapes and orientation in an external field. The second is elastic collisions between rotators. Computer calculations have demonstrated that this discrete model correctly describes the observed structural effects, eventually resulting in a “chaos-to-order” transformation. These predictions correspond to real-world experimental data obtained under different modes of deformation. We presume that the developed concept can play a central role in understanding strong nonlinear effects in the rheology of viscoelastic liquids.